Combined microwave-assisted subcritical liquid extraction of chitosan from crab shell waste - Segaran, Ramyah; Omar, Rozita; Kusumastuti, Yuni; Harun, Razif; Mustafa Kamal, Siti Mazlina (Polish Chitin Society, 2022)
Current chitosan extraction methods require a highly concentrated alkaline solvent that is costly and environmentally unfriendly. This study aimed to assess the potential of using subcritical liquid deproteination to produce amorphous chitin to reduce the alkaline concentration during the deacetylation step to obtain high-quality chitosan. A combination of microwave-assisted demineralisation, subcritical liquid (SL) deproteination, and conventional deacetylation was employed for chitosan production. Distilled water and 2% and 4% sodium hydroxide (NaOH) were used at subcritical liquid treatment temperatures of 100 to 250°C. Meanwhile, deacetylation using 20%-50% NaOH was attempted on the deproteinised chitin. 1.8 M hydrochloric acid at a 1:10 solid-to-liquid solvent ratio produced chitin with acceptable quality during microwave-assisted demineralisation. Demineralised chitin subjected to SL treatment at 150°C and 4% NaOH had the best protein removal (84.6%). Chitosan with a high degree of deacetylation (80.68%) was obtained at a lower alkalinity of 30% NaOH, derived from SL-deproteinised chitin (4% NaOH at 100°C). The crystallinity of chitin after SL treatment was reduced significantly from 72.4% to 59.4%, which allows easier access for the solvent to hydrolyse the acetamide bond. This study confirms that good quality chitosan can be produced by utilising SL treatment of demineralised chitin at a significantly short time and lower deacetylation solvent concentration.